2023
DOI: 10.1108/ijoem-05-2022-0766
|View full text |Cite
|
Sign up to set email alerts
|

The incentive effect of government subsidies on the digital transformation of manufacturing enterprises

Abstract: PurposeChina's digital economy is flourishing and playing a pivotal role in the national economy. Government subsidies, as an important tool for the national treasury, are a “reassurance” for the digital transformation of manufacturing enterprises. The purpose of this paper is to investigate the relations between the digital transformation of manufacturing enterprises and government subsidies to provide inspiration for promoting the digitization and upgrading of China's manufacturing industry and facilitate en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Government grants have been extensively studied, but few notice the difference in different government grants. Little is known about whether such grants may have heterogenous effects [ 9 11 ]. Our research aims to fill this gap in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Government grants have been extensively studied, but few notice the difference in different government grants. Little is known about whether such grants may have heterogenous effects [ 9 11 ]. Our research aims to fill this gap in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the evolutionary results of the game system also demonstrate that the widespread application of digital technologies (artificial intelligence, blockchain, cloud computing, and digital platforms) has provided corresponding technological conditions for the construction of agricultural e-commerce platforms in wholesale markets. However, there are still problems with insufficient funding [ 51 ], inadequate policies [ 52 ], and difficulty in changing purchasing and sales habits among wholesalers [ 53 ] during the construction process of these platforms. Therefore, the use of evolutionary game models and simulations is effective.…”
Section: Discussionmentioning
confidence: 99%
“…Particularly in developing countries like China, where the government still controls the allocation of resources [11,12], active CSR can improve access to resources such as government subsidies and lower bank credit rates. Empirical research has confirmed the beneficial influence of these resources on the companies' digital transformation [16,56]. For instance, an empirical study conducted by Zhao et al [16] discovered that government subsidies reduce the expenses and risk associated with digital transformation for enterprises, resulting in a significant improvement in their digitalization levels.…”
Section: The Bidirectional Relationship Between Digital Transformatio...mentioning
confidence: 97%
“…Additionally, greater organizational legitimacy facilitates firms' access to benefits such as government subsidies and lower bank credit rates [12,13], and can effectively alleviate their financing constraints [14]. Access to such resources can help to reduce the costs and risks of digital transformation and enhance companies' level of digitalization [15,16]. Therefore, does CSR, in turn, promote digital transformation in companies?…”
Section: Introductionmentioning
confidence: 99%